HEALTH ETHICS AND ADMINISTRATIVE SANCTIONS AGAINST MALPRACTICE BY DOCTORS IN INDONESIA - Wirandi Dalimunthe; Ismaidar, Ismaidar (PT. Sinergi Legal Publisher, 2025)
Malpractice is an error or negligence committed by health workers in carrying out their profession that is not in accordance with existing professional standards. This study aims to review the forms of administrative sanctions against malpractice by doctors in Indonesia based on a positive legal perspective and review the ethical aspects of health law. Ethics are crucial in the guidelines for behavior and decision-making of health workers, health law ethics include the obligations and responsibilities of a health worker in carrying out daily practice. The method used is the normative legal research method by examining existing library materials, at the level of severe malpractice doctors can be subject to sanctions in the form of revocation of practice licenses, while at other levels doctors can be subject to various forms, such as criminal sanctions, civil, administrative sanctions, and fines. Through this article, it is hoped that it will provide a comprehensive understanding of the ethics of the health profession to strengthen the moral basis in carrying out daily practice, and provide an understanding of the close relationship between ethics and health law. The conclusions of this study can be used as a guide for health practitioners, patients, and related parties to understand and apply ethics and health law as well as possible.